Binding kinetics in drug discovery - Zhang, Rumin (Henry Stewart Talks, 2020)
What is 'Binding Kinetics', The importance of binding kinetics in drug discovery, Apparent vs. intrinsic potency, Fast vs. slow binding kinetics, Binding kinetics impacts pharmacodynamics, Continuous in vitro assays for binding kinetics, Practical guidance of binding kinetics